Capabilities in the Internationalization of SMEs: A Systematic Review - Chavesta-Paico, Sheyla Johana; Jimenez-Boggio, Danna Johana; Coronel-Benites, Cynthia Vanessa (LACCEI, 2025)
Given globalization and the increasing interconnectedness of markets, internationalization has become fundamental to the growth and competitiveness of SMEs. This research aimed to explore the entrepreneurial capabilities of SMEs through a systematic literature review employing the PICO methodology in the Scopus and Web of Science databases, with a total of 1,050 articles. The PRISMA declaration was then applied, obtaining 52 articles for analysis. The findings showed that SMEs use a variety of strategies, ranging from exports to the formation of strategic alliances, adapting to their resources and the competitive environment. These capabilities, including knowledge management, innovation, marketing skills, and cultural adaptation, enable SMEs to overcome entry barriers, establish strong business relationships, and leverage the competitive advantages of internationalization. Fifty percent of studies determined that the most common problems are limited access to financial and human resources; business dynamics constitute 63% of the key capabilities that facilitate their internationalization. To overcome these challenges, it is crucial to develop key business capabilities such as innovation, digitalization, and adaptability.